Valuable Chemicals Derived from Pyrolysis Liquid Products of Spirulina platensis Residue - Siti Jamilatun; Budhijanto Budhijanto; Rochmadi Rochmadi; Avido Yuliestyan; Arief Budiman (Universitas Gadjah Mada, 2019)
With a motto of preserving nature, the use of renewable resources for the fulfillment of human needs has been seen echoing these days. In response, microalgae, a water-living microorganism, is perceived as an interesting alternative due to its easy-to-cultivate nature. One of the microalgae, which possess the potential for being the future source of energy, food, and health, is Spirulina plantesis. Aiming to identify valuable chemicals possibly derived from it, catalytic and non-catalytic pyrolysis process of the residue of S. plantesis microalgae has been firstly carried out in a fixed-bed reactor over the various temperature of 300, 400, 500, 550 and 600 °C. The resulting vapor was condensed so that the liquid product consisting of the top product (oil phase) and the bottom product (water phase) can be separated. The composition of each product was then analyzed by Gas Chromatography-Mass Spectrometry (GC-MS). In the oil phase yield, the increase of aliphatic and polyaromatic hydrocarbons (PAHs) and the decrease of the oxygenated have been observed along with the increase of pyrolysis temperature, which might be useful for fuel application. Interestingly, their water phase composition also presents some potential chemicals, able to be used as antioxidants, vitamins and food additives.